2009
DOI: 10.1111/j.1365-2249.2009.03956.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of innate immune responses by vasoactive intestinal peptide (VIP): its therapeutic potential in inflammatory disease

Abstract: Summary Since the late 1970s a number of laboratories have studied the role of vasoactive intestinal peptide (VIP) in inflammation and immunity. These studies have highlighted the dramatic effect of VIP on immune cell activation and function, and studies using animal models of disease have indicated that VIP has significant therapeutic and prophylactic potential. This review will focus on the effects of VIP on innate immune cell function and discuss the therapeutic potential for VIP in inflammatory diseases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 89 publications
0
51
0
1
Order By: Relevance
“…In the immune system, VIP can modulate both innate and adaptive immunity, showing predominantly anti-inflammatory and immunomodulatory actions. In vivo mouse data indicate that VIP treatment may have a promising role in the treatment of inflammatory and autoimmune diseases (Delgado, 2001;Gomariz, 2006;Lodde, 2006;Arranz, 2008;Calafat, 2009;Smalley, 2009;Gomariz, 2010). In several animal models of inflammation and autoimmune diseases, it has been described that VIP decreases cytokine expressions related to Th17 cells (Abad, 2005;Leceta, 2007;Jimeno, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the immune system, VIP can modulate both innate and adaptive immunity, showing predominantly anti-inflammatory and immunomodulatory actions. In vivo mouse data indicate that VIP treatment may have a promising role in the treatment of inflammatory and autoimmune diseases (Delgado, 2001;Gomariz, 2006;Lodde, 2006;Arranz, 2008;Calafat, 2009;Smalley, 2009;Gomariz, 2010). In several animal models of inflammation and autoimmune diseases, it has been described that VIP decreases cytokine expressions related to Th17 cells (Abad, 2005;Leceta, 2007;Jimeno, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We here found that lowest levels of CGRP and VIP in kidney tissues were found in papillary RCC. In addition to its direct anti-tumoral effects [29], VIP and analogues are considered for treatment of autoimmune and inflammatory diseases [35]. Hence local inhibition of peptidergic system in papillary type RCC may partly be responsible from resistance to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies have also identified a pathway that inhibits nuclear entry of NF-κB through VPAC signaling, which inhibits IκB phosphorylation (cAMP-independent pathway). shows a graphical representation of VIP signal transmission and the expected regulatory activity of the inflamematory reactions [47,48].…”
Section: Signal Transductionmentioning
confidence: 99%